Defining sustainability in Afghanistan’s built environment: a case study of world bank building in Kabul and comparative analysis of prominent literature - Khatibi, Mahsa (International Information and Engineering Technology Association, 2021)
The built environment is one of the critical areas of intervention for sustainable development. This study aims to investigate the sustainable and appropriate ways of designing Afghanistan’s built environment. To put forward a reliable mechanism of research, the study develops and uses three approaches. The first is to review the sustainable strategies applied in the design of the country’s first LEED-certified building, the World Bank Building in Kabul (WBBK). Secondly to understand the main concepts involved in the practice of designing for sustainability by analyzing five of the most influential books in the realm of design and sustainability. Finally, the findings from the review of the five books are reinforced with more literature associated with design and sustainability to analyze and evaluate the sustainable strategies of the WBBK. The study posits that although the building can promote the idea of a sustainable built environment in the country but there are several issues. Among the issues are, (1) Its high dependence on eco-technologies to reduce environmental impact rather than designing in relation to social and ecological systems, (2) Its insufficiency in providing a resilient design that is self-sufficient, flexible, and adaptive, and (3) Its lack of creating aesthetic experiences and cultural meaning for its occupants which are required for future designs and development. Furthermore, based on the findings and upon inquiring into the sustainable design of WBBK, the paper concluded with a set of recommendations to contribute towards the design of a sustainable built environment in Afghanistan.